Square roots and calculus

Calculus Level 5

Let function f ( x ) = a ln x + x + 1 f(x)=a \ln x + \sqrt{x+1} for x > 0 x>0 , where a a is a real number and a 0 a \neq 0 .

If x [ 1 e 2 , + ) \forall x \in \left[\dfrac{1}{e^2},+\infty\right) , f ( x ) x 2 a f(x) \le \dfrac{\sqrt{x}}{2a} , what is the maximum value of a a ?

Let A A denote the maximum value of a a . Submit 10000 A \lfloor 10000A \rfloor .

If you manage to solve this problem, show your real analysis proof.


The answer is 3535.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Joël Ganesh
Aug 31, 2019

Plugging in x = 1 x=1 in the inequality f ( x ) x 2 a f(x) \leq \frac{\sqrt{x}}{2a} shows us that 2 1 2 a \sqrt{2} \leq \frac{1}{2a} , from which follows that a 1 2 2 . a \leq \frac{1}{2\sqrt{2}}. This choice x = 1 x=1 might be pretty random at first glance, but remember that ln ( 1 ) = 0 \ln(1)=0 , which makes the inequality easier to deal with.

We will now show that the upperbound, a = 1 2 2 a = \frac{1}{2\sqrt{2}} , will satisfy the conditions given. We will do this using the following theorem: Let b R b\in\mathbb{R} , and let f , g : [ b , ) R f, g: [b, \infty) \to \mathbb{R} be differentiable functions on their domain. If f ( b ) g ( b ) f(b) \leq g(b) , lim x ( g ( x ) f ( x ) ) 0 \lim_{x\to\infty} \left(g(x) - f(x)\right) \geq 0 and there exists x 0 [ b , ) x_0\in [b, \infty) , such that f ( x 0 ) = g ( x 0 ) f(x_0)=g(x_0) and furthermore f ( x ) g ( x ) f'(x) \geq g'(x) for x [ b , x 0 ] x \in [b, x_0] and f ( x ) g ( x ) f'(x) \leq g'(x) for x [ x 0 , ) x \in [x_0, \infty) , then f ( x ) g ( x ) f(x) \leq g(x) for all x [ b , ) x \in [b, \infty) .

We will come to this fact via a proof by contradiction. Suppose that there exists x 1 [ b , ) x_1 \in [b, \infty) such that f ( x 1 ) > g ( x 1 ) f(x_1) > g(x_1) . Without loss of generality, assume that x 1 [ b , x 0 ] x_1 \in [b, x_0] . Then, because f ( x ) g ( x ) f'(x) \geq g'(x) for all x [ b , x 0 ] x \in [b, x_0] , we notice that f ( x 0 ) > g ( x 0 ) f(x_0) > g(x_0) , leading to a contradiction, as f ( x 0 ) = g ( x 0 ) f(x_0) = g(x_0) . \blacksquare

We will be using this theorem with b = 1 e 2 b = \frac{1}{e^2} , f ( x ) = ln ( x ) 2 2 + x + 1 f(x) = \frac{\ln(x)}{2\sqrt{2}} + \sqrt{x+1} and g ( x ) = x 2 ( 1 2 2 ) = 2 x g(x) = \frac{\sqrt{x}}{2\left(\frac{1}{2\sqrt{2}}\right)} = \sqrt{2x} , furthermore, we use x 0 = 1 x_0 = 1 . However, we will have to check if the conditions are satisfied.

Note that because e > 2 e > 2 we have that f ( 1 e 2 ) = 1 e 2 + 1 2 2 < 5 4 2 2 = 5 2 2 f(\frac{1}{e^2}) = \sqrt{\frac{1}{e^2}+1} - \frac{\sqrt{2}}{2} < \sqrt{\frac{5}{4}} - \frac{\sqrt{2}}{2} = \frac{\sqrt{5}-\sqrt{2}}{2} . Now, notice that ( 9 4 ) 2 = 81 16 > 5 \left(\frac{9}{4}\right)^2 = \frac{81}{16} > 5 and 1. 4 2 < 2 1.4^2 < 2 , so that 5 2 2 < 9 8 0.7 = 9 12.5 70 100 < 43 100 \frac{\sqrt{5}-\sqrt{2}}{2} < \frac{9}{8}-0.7 = \frac{9\cdot 12.5 - 70}{100} < \frac{43}{100} . Furthermore, notice that because e < 3 e < 3 , g ( 1 e 2 ) = 2 e > 2 3 > 1.4 3 = 1.4 33 99 > 46 100 > 43 100 g(\frac{1}{e^2}) = \frac{\sqrt{2}}{e} > \frac{\sqrt{2}}{3} > \frac{1.4}{3} = \frac{1.4\cdot 33}{99} > \frac{46}{100} > \frac{43}{100} , so that we can conclude that f ( 1 e 2 ) g ( 1 e 2 ) f(\frac{1}{e^2}) \leq g(\frac{1}{e^2}) .

Now we will show that lim x ( g ( x ) f ( x ) ) = lim x ( 2 x ln ( x ) 2 2 x + 1 ) 0 \lim_{x\to\infty} \left(g(x) - f(x)\right) = \lim_{x\to\infty} \left(\sqrt{2x} - \frac{\ln(x)}{2\sqrt{2}} - \sqrt{x+1}\right) \geq 0 . Notice that lim x ( 2 x ln ( x ) 2 2 x + 1 ) = lim x ( ( 2 1 ) x ln ( x ) 2 2 ) \lim_{x\to\infty} \left(\sqrt{2x} - \frac{\ln(x)}{2\sqrt{2}} - \sqrt{x+1}\right) = \lim_{x\to\infty} \left((\sqrt{2}-1)\sqrt{x} - \frac{\ln(x)}{2\sqrt{2}}\right) . With l'Hôpital's rule we can show that lim x ln ( x ) x = 0 \lim_{x\to\infty} \frac{\ln(x)}{\sqrt{x}} = 0 , so that in the limit ln ( x ) \ln(x) can be neglected and lim x ( g ( x ) f ( x ) ) 0 \lim_{x\to\infty} \left(g(x) - f(x)\right) \geq 0 .

Note that f ( 1 ) = g ( 1 ) f(1) = g(1) per definition of a a , so we can skip this. However, we still have to show that f ( x ) g ( x ) f'(x) \geq g'(x) for x [ 1 e 2 , 1 ] x \in [\frac{1}{e^2}, 1] and f ( x ) g ( x ) f'(x) \leq g'(x) for x [ 1 , ) x \in [1, \infty) . Note that f ( x ) = 1 2 x 2 + 1 2 x + 1 f'(x) = \frac{1}{2x\sqrt{2}} + \frac{1}{2\sqrt{x+1}} and g ( x ) = 1 2 x g'(x) = \frac{1}{\sqrt{2x}} .

Now that we have this out of the way, let us show that for x [ 1 e 2 , 1 ] : f ( x ) g ( x ) x \in [\frac{1}{e^2}, 1] : f'(x) \geq g'(x) . Because x [ 1 e 2 , 1 ] x \in [\frac{1}{e^2}, 1] we have that x 2 1 , from which follows that x 2 + 2 x + 1 = ( x + 1 ) 2 2 ( x + 1 ) so that 0 x + 1 = x + 1 2 ( x + 1 ) . x^2 \leq 1, \text{ from which follows that } x^2+2x+1 = (x+1)^2 \leq 2(x+1) \text{ so that } 0 \leq |x+1| = x+1 \leq \sqrt{2(x+1)}. If we go further, we notice that 2 x ( x + 1 ) = 2 x 2 + 2 x 2 x 2 ( x + 1 ) , so that 2 x 2 + 3 x 1 + 2 x 2 ( x + 1 ) x + 2 x 2 ( x + 1 ) . 2x(x+1) = 2x^2+2x \leq 2x\sqrt{2(x+1)}, \text{ so that } 2x^2 + 3x \leq 1 + 2x\sqrt{2(x+1)} \leq x + 2x\sqrt{2(x+1)}. The last step follows from 1 x 1 \leq x . By adding 2 x 2 + 2 x 2x^2 +2x to both sides, we notice that 4 x 2 + 4 x ( x + 1 ) 2 + 2 ( x 2 ) ( x + 1 ) + ( x 2 ) 2 = ( x + 1 + x 2 ) 2 4x^2+4x \leq (\sqrt{x+1})^2+2(x\sqrt{2})(\sqrt{x+1})+(x\sqrt{2})^2 = (\sqrt{x+1}+x\sqrt{2})^2 Taking the square root on both sides gives us 0 2 x ( x + 1 ) x + 1 x 2 , from which follows that f ( x ) g ( x ) . 0 \leq 2\sqrt{x(x+1)} - \sqrt{x+1} \leq x\sqrt{2}, \text{ from which follows that } f'(x) \geq g'(x). The last step requires a couple of relatively easy steps, which I leave for the reader. Likewise can be shown that for x [ 1 , ) : f ( x ) g ( x ) x \in [1, \infty): f'(x) \leq g'(x) , as then x 2 1 x^2 \geq 1 . With this, we can use the specified theorem to notice that a = 1 2 2 a = \frac{1}{2\sqrt{2}} satisfies. Remember that a 1 2 2 a \leq \frac{1}{2\sqrt{2}} , so that A = 1 2 2 A = \boxed{\frac{1}{2\sqrt{2}}} .

Matteo Bianchi
Aug 28, 2019

We know that aln(x) + \sqrt{x + 1} is less or equal to \frac{\sqrt{x}}{2a} for x greater or equal to e^{-2}, and,in particular, for x = 1. Substituting x = 1 in the inequality we get aln(1) + \sqrt{2} less or equal to \frac{\sqrt{1}}{2a}. Solving for a we get that a is less or equal to \frac{1}{2\sqrt{2}} . So A = \frac{1}{2\sqrt{2}} and the solution is \boxed{3535}

OK. I wonder why would you substitute x=1 for the first place just because it would make the calcluation easier? It's not a rigorous proof.

Alice Smith - 1 year, 9 months ago

Log in to reply

Why not? I used the informations i had to semplify the process. I think it's fair and rigorous: you are not proving a theorem, you are just evaluating the value of a number

Matteo Bianchi - 1 year, 9 months ago

Log in to reply

Then how do you prove that it is also true for other x in range [ 1 e 2 , + ) [\dfrac{1}{e^2},+\infty) ?

Alice Smith - 1 year, 9 months ago

wonderfullllllllll

Kolla Gowtham kishore - 1 year, 8 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...